Venomous Snakes and Lizards of New Mexico - Brandon M. Bourassa; Steve A. Johnson; Max D. Havelka; Basil V. Iannone (EDIS)
New Mexico is home to many incredible and unique landscapes inhabited by many equally incredible animals. Some of these animals, however, may be an unwelcome sight to many visitors and residents of the Land of Enchantment. Eleven venomous snakes and one venomous lizard call New Mexico home. This document presents information on identification, range, and natural history of the fascinating reptiles.